AB0181 Sonographic Persistence of Subclinical Joint and Tendon Inflammation in Rheumatoid Arthritis Patients Achieving Sustained Clinical Remission on Synthetic or Biologic Drug Therapy: Preliminary Data of A Cross-Sectional Study. (15th July 2016) - Becciolini, A.; Favalli, E.G.; Di Carlo, M.; Biggioggero, M.; Crotti, C.; Salaffi, F.; Meroni, P.L.
Abstract : Background: Based on more recent recommendations, remission or low-disease activity are pivotal targets to be achieved in the treatment of rheumatoid arthritis (RA). However, despite a clinical remission, subclinical joint and tendon inflammation potentially leading to structural and functional worsening can be detected in a large number of patients. Objectives: To determine the prevalence of joint and tendon inflammation by ultrasound (US) gray scale (GS) and power Doppler (PD) in RA patients treated with biological (bDMARDs) or synthetic disease modified anti-rheumatic drugs (sDMARDs) achieving a sustained clinical remission. Methods: RA patients treated with sDMARDs or bDMARDs achieving a sustained clinical remission (defined as DAS28<2.6 since at least 6 months and no swollen joints) were prospectively selected from two Rheumatology Departments. All subjects underwent US examination of hands and wrists bilaterally. The US evaluation was performed on 22 joints (bilateral proximal interphalangeal, metacarpophalangeal and wrists) and 26 tendons/tendon compartments with synovial sheath (first through sixth wrist extensor compartments, first through fifth finger flexor digitorum superficialis and profundus tendons, flexor radialis carpi, and flexors digitorum at the carpal tunnel). The presence of synovial/tenosynovial effusion or hypertrophy in GS and pathological hypervascularization at PD were reported and graded based on a semi-quantitative scoring system: none, mild, moderate and severe (0 to 3). The two treatment groups were compared by Fisher exact test. Results: Forty-eight RA patients were enrolled (20 on bDMARDs and 28 on sDMARDs). A total of 1056 joints and 1248 tendons/tendon compartments with synovial sheath were examined. Twenty-seven (56.2%) patients presented at least one joint with GS synovial effusion or hypertrophy (9/20 in bDMARD and 16/28 in sDMARD group, respectively; p=0.559). In 15 (31.2%) patients we found at least one joint with active PD signal (7/20 in bDMARD and 8/28 in sDMARDs group, p=0.755). In 8 (16.7%) patients at least one tendon sheath with GS synovial effusion or hypertrophy (2/20 treated with bDMARDs and 6/28 with sDMARDs, respectively; p=0.440) was reported. No patients presented at least one tendon sheath with active PD signal in bDMARD group and 3/28 in sDMARD group (p=0.255). Finally, GS alterations were significantly more frequent in the dominant hand compared to the contralateral (22 [45.8%] vs 10 [20.8%], p=0.017). Conclusions: Our data confirmed the high prevalence of US-detected subclinical active synovitis/tenosynovitis in RA patients achieving a sustained DAS28 remission. Joints resulted more frequently involved than tendons in subclinical detected inflammatory process. No differences were found according with bDMARD or sDMARD treatment. GS synovitis was more frequently demonstrated in the dominant hand. Disclosure of Interest: None declared